climateStability: An R package to estimate climate stability from time-slice climatologies - Owens, Hannah Lois; Guralnick, Robert (Biodiversity Informatics, 2019)
As continental and global-scale paleoclimate model data become more readily available, biologists can now ask spatially explicit questions about the tempo and mode of past climate change and the impact of those changes on biodiversity patterns. In particular, researchers have focused on climate stability as a key variable that can drive expected patterns of richness, phylogenetic diversity and functional diversity. Yet, climate stability measures are not formalized in the literature and tools for generating stability metrics from existing data are nascent. Here we define “deviation” of a climate variable as the mean standard deviation between time slices over time elapsed; “stability” is defined as the inverse of this deviation. Finally, climate stability is the product of individual climate variable stability estimates. We also present an R package, climateStability, which contains tools for researchers to generate climate stability estimates from their own data.